Analisis Sifat Mekanik Material Baja Karbon Rendah ST 37 Akibat Dari Pengujian Tarik Berdasarkan Data Manual dan Komputer - Imam Prabowo; Muhammad Ichsanudin (Journal of Metallurgical Engineering and Processing Technology, 2022)
ST 37 Steel is categorized as a low carbon steel which has a composition of carbon around0.005 to 0.3% weight. It has good ductility, flexibility, weldability and formability so can be applied for automotive industry’s components as well as material constructions. Unfortunately, it does not possess an excellent hardness and wear resistance. In this research, ST 37 was subjected to tensile testing to understanding its mechanical properties of ST 37 Steel by comparing the data obtained from manual and computerized procedures. The tensile testing was conducted by Universal Testing Machine (Tarno Grocki), applying ASTM E8/E8M. The results of the experiments revealing the ultimate tensile strength of ST 37 Steel based on computerized and manual procedures are 524,03 MPa and 511,44 Mpa respectively. In addition, the Young modulus of ST 37 Steel based on computerized and manual procedures are 524,03 MPa and 511,44 Mpa respectively. In addition, the Young modulus of manual and computerized procedures are 16,338 GPa and 3,598 Gpa consecutively. Moreover, the yield strength was 411,03 Mpa. The differences between manual and computerized procedures were due to sampling time, parallax and cosine errors and the distinct number of data. Furthermore, the surface of the material after tensile testing showed ductile fracture mechanism in which the fracture was shaped like a cup and cone and formed an angle of 45o. The surface is also displaying a filamentous shape because of the tensile force.